Association between systemic inflammation biomarkers and cancer cachexia in patients with gastric cancer: a cross-sectional study - Huang, Yan; Zhang, Jinxin; Ge, Yan; Wang, Chen; Wang, Xiuhua; Zuo, Junbo (Frontiers in Nutrition, 2026)
BackgroundSystemic inflammation is regarded as a key driver of cancer cachexia. This study aimed to explore the relationship between systemic inflammatory biomarkers and cancer cachexia and compare their predictive capabilities in patients with gastric cancer (GC).MethodsCancer cachexia was diagnosed according to Asian Working Group for Cachexia (AWGC) criteria. Logistic regression analyses were utilized to evaluate the association between systemic inflammation biomarkers and cancer cachexia. The receiver operating characteristic curve was used to assess the predictive performance of these biomarkers in identifying cancer cachexia.ResultsA total of 440 patients were included in this study. Among them, 167 patients (37.95%) were diagnosed with cachexia. In GC patients with cachexia, systemic inflammation biomarkers including neutrophil-to-lymphocyte ratio (NLR), systemic immune-inflammation index (SII), systemic inflammatory response index (SIRI), aggregate index of systemic inflammation (AISI), inflammatory prognostic index (IPI), and inflammatory burden index (IBI) were significantly elevated, while the advanced lung cancer inflammation index (ALI) was significantly decreased (all p < 0.001). After adjusting for potential confounding variables, all these systemic inflammation biomarkers were significantly associated with cancer cachexia (all p < 0.001). According to the Delong test, ALI showed the highest AUC (AUC = 0.746, 95%: 0.698–0.794) compared with the other systemic inflammation biomarkers (all p < 0.05).ConclusionOur findings demonstrated that NLR and NLR-related systemic inflammatory biomarkers (SII, SIRI, AISI, IPI, IBI, and ALI) were significantly associated with cancer cachexia. Among these biomarkers, ALI exhibited the highest efficacy in identifying GC patients with cancer cachexia.